Ambipolar thermoelectric power of chemically-exfoliated RuO2 nanosheets. (5th December 2017) - Kim, Jeongmin; Yoo, Somi; Moon, Hongjae; Kim, Se Yun; Ko, Dong-Su; Roh, Jong Wook; Lee, Wooyoung
Abstract: The electrical conductivity and Seebeck coefficient of RuO2 nanosheets are enhanced by metal nanoparticle doping using Ag-acetate solutions. In this study, RuO2 monolayer and bilayer nanosheets exfoliated from layered alkali metal ruthenates are transferred to Si substrates for device fabrication, and the temperature dependence of their conductivity and Seebeck coefficients is investigated. For pristine RuO2 nanosheets, the sign of the Seebeck coefficient changes with temperature from 350–450 K. This indicates that the dominant type of charge carrier is dependent on the temperature, and the RuO2 nanosheets show ambipolar carrier transport behavior. By contrast, the sign of the Seebeck coefficient for Ag nanoparticle-doped RuO2 nanosheets does not change with temperature, indicating that the extra charge carriers from metal nanoparticles promote n-type semiconductor behavior.